DEVELOPMENT OF NOVEL TOTAL INTRAVENOUS ANESTHESIA PROTOCOL USING CONSTANT RATE INFUSION IN GOATS DURING PAIN MANAGEMENT - M. Asif; M. A. Khan; H. Akbar; M. O. Omer (Journal of Animal and Plant Sciences, 2022)
The study was aimed to develop a suitable total intravenous anesthesia protocol by comparative efficacy of three different combinations of detomidine, midazolam, propofol and ketamine in goats undergoing rumenotomy. In total, 18 female goats were divided into 3 treatment groups A, B and C comprising 6 animals each. In Group-A, after sedation with detomidine @ 2.5 µg/kg, induction was achieved with propofol @ 4 mg/kg and maintenance with constant rate infusion of (detomidine 2.5 µg/kg/hr + propofol 9.6 mg/kg/hr). Similarly, in Group-B, after sedation with midazolam @ 0.25 mg/kg, induction was done with ketamine @ 4 mg/kg and maintenance with infusion of (midazolam 0.25 mg/kg/hr + ketamine 2.4 mg/kg/hr). Whereas, in Group-C, after sedation with (detomidine1.25 µg/kg + midazolam 0.12 mg/kg), induction was done with (propofol 2 mg/kg + ketamine 2 mg/kg) and maintenance with combination of all drugs (detomidine 1.2 µg/kg/hr + midazolam 0.12 mg/kg/hr + propofol 4.5 mg/kg/hr + ketamine 1.2 mg/kg/hr) using a syringe-driving pump. Anesthetic, clinico-physiological and haematobiochemical parameters were evaluated. A better quality anesthesia with rapid and smooth induction, excellent muscle relaxation and rapid recovery was noticed in group C than group A and B. The statistical analysis indicated significant differences (p<0.05) for heart & respiratory rates, diastolic arterial pressure, partial pressure of oxygen and oxygen hemoglobin saturation among or within all groups except within group C. However, non-significant differences (p>0.05) were observed among or within all groups for packed cell volume, total erythrocyte count, total plasma protein and liver & renal function parameters. In conclusion, total intravenous anesthesia maintained with detomidine-midazolam-propofol-ketamine proved to be the best drug combinations taking into account the anesthetic, clinico-physiological and haematobiochemical parameters during pain management.
Keywords: Detomidine; midazolam; propofol; ketamine; constant rate infusion; goat